MODEL EKSPLORASI BAKAT UNTUK MENINGKATKAN KEMATANGAN KARIR ANAK BINAAN DI LPKA MEDAN - Suri Mutia Siregar; Hasnida Hasnida; Ika Sari Dewi; Ade Rahmawati Siregar; Afra Munira (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
Juvenile offenders are aged between 12 and 18 years old and are in conflict with the law. Based on field findings, data showed that juvenile offenders have limited access to education in correctional institutions. Several factors contributing to this situation include: (1) a schedule that does not align with formal school hours; (2) limited facilities and resources for learning; and (3) inadequate educational backgrounds due to insufficient parental attention or financial constraints prior to entering the correctional facility. If not addressed promptly, this situation is expected to hinder their ability to adapt to society after leaving the correctional institution. This service aims to develop a special talent exploration model to enhance career maturity among juvenile offenders. The methods used consist of four main components: (1) interest and talent assessment; (2) career orientation psychoeducation; (3) career planning training; and (4) individual counseling on interests and talents. The results of the service show that the majority of juvenile offenders are better suited for simple and routine jobs. Further findings revealed that most of them have a practical and concrete way of thinking and a primary interest in three fields: social work, music/arts, and fieldwork.